Nonparametric statistical methods - Hollander, Myles; Wolfe, Douglas A.; Chicken, Eric, 1963- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"In this third edition we have improved the eleven chapters of the second edition and added five new chapters. Also organized all of the R programs used in this third edition into a documented collection that is formally registered as an R package specifically linked to this third edition. "--
"Written by leading statisticians, this new edition has been completely updated to include additional modern topics and procedures, more real-world data sets, and more problems from real-life situations. Incorporating the R software program, this user-friendly book provides readers with an arsenal of nonparametric techniques, helping them develop the insight needed to choose appropriate procedures for various situations. It features five new chapters with added-on topics including Density Estimation, Kernel Regression, Nonparametric Regression, Ranked-Set Sampling, and Bayesian Nonparametrics"-- Provided by publisher.
Includes bibliographical references and indexes.
Description based on print version record and CIP data provided by publisher.
Keywords: Nonparametric statistics; MATHEMATICS / Probability & Statistics / General; Nonparametric statistics; Electronic books